The Role of Self-Esteem in Predicting Parent-Child Relationships and Students' Emotion Regulation: A Structural Equation Modeling Approach - Muntamah, Bening Siti; Wulandari, Primatia Yogi; Suminar, Dewi Retno; Pratama, Muhammad Fikri; Ulwiyyyah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
Adolescents with risky behaviors often struggle to regulate their emotions adaptively. Emotion regulation is essential for helping adolescents evaluate and respond to emotional situations in a healthy manner. Parent-child relationships and self-esteem have been found to influence these regulation abilities. This study aimed to examine whether self-esteem mediates the relationship between adolescents’ perceptions of parent-child relationships and their use of emotion regulation strategies. This quantitative research involved 214 junior high school students identified with tendencies toward risky behavior, using a cross-sectional design and convenience sampling. Data were analyzed using Structural Equation Modeling (SEM) with IBM AMOS 24. The results showed that self-esteem partially and fully mediated the relationship between parent-child relationships and emotion regulation strategies, including Cognitive Reappraisal and Expressive Suppression. These findings highlight the significance of enhancing family-based interventions and fostering adolescent self-esteem to support effective emotion regulation, particularly for those at risk of maladaptive behavior.